Modern-Day Xenophobia Critical Historical and Theoretical Perspectives on the Roots of Anti-Immigrant Prejudice - Yakushko, Oksana (Springer International Publishing, 2018)
This book engages the topic of xenophobia from both psychological and socio-political approaches. Recently, xenophobia as a social standpoint or social attitude has come under increased scrutiny by the public, scholars, and educators; however, few works have directly summarized current theories of xenophobia as well as articulated critical perspectives on the issue. This work provides an overview of the concept, historical factors related to its development, and a review of varied theoretical perspectives. The intertwining of psychological and sociological perspectives allows the author to present a multi-dimensional, multi-layered argument in a way which effectively prevents any attempt to apply any one single over-arching theory, and thus effectively presents the complexity of the topic at hand.